Fuzzy logic and soft computing applications : 11th International Workshop, WILF 2016, Naples, Italy, December 19-21, 2016, Revised selected papers /: 11th International Workshop, WILF 2016, Naples, Italy, December 19-21, 2016, Revised selected papers. (2017) - Unknown
No abstract available